2012
DOI: 10.1902/jop.2011.110187
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Risk Assessment Model in a Sample of Regular and Irregular Compliers Under Maintenance Therapy: A 3‐Year Prospective Study

Abstract: The risk profile influenced the recurrence of periodontitis and tooth loss. RCs had less recurrence of periodontitis and less tooth loss. The PRA model can be useful in particularizing the risk of patients and adjusting recall intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 33 publications
10
86
1
Order By: Relevance
“…The definition of compliers and non-compliers was according to Costa et al, 2012, compliers being considered those showing 100% cooperation with the recall visits interval suggested by the periodontist. Non-compliers were considered those that lost any regular visit but continued, irregularly, with their PMP appointments (7).…”
Section: Methodsmentioning
confidence: 99%
“…The definition of compliers and non-compliers was according to Costa et al, 2012, compliers being considered those showing 100% cooperation with the recall visits interval suggested by the periodontist. Non-compliers were considered those that lost any regular visit but continued, irregularly, with their PMP appointments (7).…”
Section: Methodsmentioning
confidence: 99%
“…It appears that there is a reasonable need to research further the very basis of such a suggested interval. An increasing number of studies [47][48][49][50][51] have highlighted the importance of utilizing risk-based models to identify patients at higher risk with some promising developments being made in this arena. The Periodontal Risk Calculator (PRC) was introduced 47 by Page et al Based on mathematically derived algorithms it assigns relative weights to the various known risks that may increase patients' susceptibility to develop periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Another tool described by Lang and Tonetti 49 as Periodontal Risk Assessment (PRA) is of some relevance here. Using known risk factors/indicators in each individual patient, it aims to enable the practitioner to determine the frequency and extent of professional support necessary to maintain periodontal health following active therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding how to determine the maintenance interval in SPT is still weak [6]. A popular and valid approach is based on the risk assessment approach proposed by Lang and Tonetti [7], who defined several risk parameters, including BOP, PPD, tooth loss, age-related bone loss, systemic diseases, and environment/smoking [8]. However, different approaches have been discussed, considering additional diagnostics as a way to improve the validity of risk-oriented maintenance estimation [6283031].…”
Section: Discussionmentioning
confidence: 99%
“…The classical parameters that serve as a basis for risk assessment are periodontal probing depth (PPD), bleeding on probing (BOP), bone loss in relation to the patient's age, tooth loss, records of pre-existing systemic diseases (e.g., diabetes), and environmental risk factors, such as smoking habits [7]. After the completion of initial treatment, individualized intervals of SPT are determined by evaluating these parameters according to existing definitions [89]. However, the evidence supporting specific maintenance intervals for patients receiving SPT is still weak [6].…”
Section: Introductionmentioning
confidence: 99%